Relevansi Anggaran Pendidikan dengan Capaian Indeks Pembangunan Manusia Dimensi Pendidikan - Sanisah, Siti (Universitas Negeri Malang, 2023)
Abstract: The purpose of this study was to determine the relevance of the education budget to the achievement of the HDI education dimension in Central Lombok Regency. This naturalistic research data was obtained through focused synthesis, documentation, literature study and questionnaires which were analyzed through data reduction, data display, and conclusion drawing. The results showed that the relevance index reached 0,35% (less relevant), because the financing programs and educational activities were not in line with the grand design of education. The achievement of RLS is low (6.29) and HLS (13.87) which has an impact on the minimum education index (0.59). What is indicated to have an influence is the goodwill and political will of the government, sources of education budget, connectivity to education planning, implementation of educational programs and activities, management of education financing and commitment of education managers guided by good governance. Keywords: relevance; education budget; HDI dimensions of education Abstrak: Tujuan penelitian ini adalah mengetahui relevansi anggaran pendidikan dengan capaian IPM dimensi pendidikan di Kabupaten Lombok Tengah. Data penelitian naturalistik ini diperoleh melalui sintesis terfokus, dokumentasi, studi kepustakaan dan angket yang dianalisis melalui reduksi data, display data, verifikasi dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa indeks relevansi mencapai 0,35% (kurang relevan), karena pembiayaan program dan kegiatan pendidikan tidak sejalan dengan grand design pendidikan. Capaian RLS menjadi rendah (6,29) dan HLS (13,87) yang berimbas pada minimya indeks pendidikan (0,59). Faktor yang terindikasi mempengarui adalah good will dan political will pemerintah, sumber anggaran pendidikan, konektivitas perencanaan pendidikan, kejelasan program dan kegiatan pendidikan, manajemen pembiayaan pendidikan serta komitmen pengelola urusan pendidikan yang berpedoman pada good governance. Kata kunci: relevansi; anggaran pendidikan; IPM dimensi pendidikan